Expert System for Fetal Heart Rate Measuring Devices: Literature Review - Susmiyati, Susmiyati; Widyawati, Melyana Nurul; Kurnianingsih, Kurnianingsih (Indonesian Journal of Global Health Research, 2024)
With the current development of science and technology, many fetal heart rate detection devices have been designed and have become superior in the field of technology. The aim of the literature study is to find out which expert systems have been developed to detect fetal heartbeats. This research method is a literature study, with a search using Evidence Based Practice (EBP) from the Google Scholar data base. There are 10 articles based on searching results using the PICO technique for the last 5 years from 2019-2023. After conducting an article search, 10 research articles were selected that met the inclusion criteria. The results of the analysis found that there are several expert systems that have been developed to detect fetal heartbeats, including: Android-based, Bluetooth low energy, LabVIEW, Telefetalcare system, Blind Source Separation, smartwatch, Demster-Shafer, Phantom, Arduino Uno, and ATMega8 microcontroller. It was concluded that the health sector system had developed a lot.